2007
DOI: 10.1021/cg070252c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Netted Sphere-like CdS Nanostructures

Abstract: Netted sphere-like CdS nanostructures consisting of the dentritic nanolines were prepared in ethylenediamine using L-cysteine and cadmium nitrate tetrahydrate as precursors by a solvothermal process at 150 °C for 8 h. The reaction time, the molar ratio of precursors, solvent, and temperature can be used as the additional means to control the size and morphology. The synthesized product was characterized by X-ray powder diffraction (XRD), Fourier transform-infrared (FT-IR) spectroscopy, Field emission scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…Therefore, the S-C bond in diphenylthiocarbazone is easily ruptured during the solvothermal process, owing to high Journal of Nanoscience temperature and pressure, causing the formation of PbS nuclei. The adjacent EDA molecules are readily covered on the surface of newly generated PbS crystals which serve as building unit for the formation of hierarchical PbS microstars with multidendritic arms via highly epitaxial crystal growth [38][39][40][41]. This assumption is confirmed by the control experiments regarding the mixed solvents with various components and also agrees well with the growth of CdS nanorods in the literature [38,42].…”
Section: Growth Mechanismsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the S-C bond in diphenylthiocarbazone is easily ruptured during the solvothermal process, owing to high Journal of Nanoscience temperature and pressure, causing the formation of PbS nuclei. The adjacent EDA molecules are readily covered on the surface of newly generated PbS crystals which serve as building unit for the formation of hierarchical PbS microstars with multidendritic arms via highly epitaxial crystal growth [38][39][40][41]. This assumption is confirmed by the control experiments regarding the mixed solvents with various components and also agrees well with the growth of CdS nanorods in the literature [38,42].…”
Section: Growth Mechanismsupporting
confidence: 86%
“…The initial nucleation will minimize the system energy, while the subsequent crystal growth would strongly determine the final shapes of the crystals by controlling kinetic and/or thermodynamic parameters [14]. As known, EDA molecules contain two -NH 2 groups, which can coordinate with cations, and thereby facilitates the growth of the crystals with desired morphologies [1,38]. Meanwhile, EDA can influence the epitaxial growth, which can firstly incorporate into the inorganic skeleton and then escape to form crystals with desired shapes [38][39][40][41].…”
Section: Growth Mechanismmentioning
confidence: 99%
“…Growth mechanism L-cys molecule consists of several functional groups such as -COOH, -NH 2 , and -SH, which have a strong tendency to coordinate with inorganic cations and metals [22]. By mixing L-cys and Sn 4+ solution, Sn 4+ can interact with L-cys molecules to form precursor complexes.…”
Section: Resultsmentioning
confidence: 99%
“…With the breaking of the S-C bond in L-cys, S 2− ions would be released under high temperature and high pressure by hydrothermal heating [22]. In order to unveil the growth mechanism of the flower-like SnS 2 hierarchical structures (S5), structural dependence of the samples on growth time has been Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the results, the intense peak is at 505 nm because of the near-band-edge emission of CdS, whereas a very low intensity broad peak centered at 670 nm is attributed to the structure defects, ionized vacancies, or impurities. Zhao et al reported the photoluminescence properties of netted sphere-like CdS nanostructures with a broad emission peak at 570 nm and a weak shoulder at 610 nm associated with the sulfur vacancies, extrinsic defects, or impurities [37]. Differences in optical properties have been researched widely, and the results indicate that they mainly come from different shapes, sizes and phase structures of the semiconductor nanocrystals.…”
Section: Resultsmentioning
confidence: 99%